SUPERVISION OF ENVIRONMENTAL POLLUTION BY THE ENVIRONMENTAL AGENCY OF SIAK REGENCY (CASE STUDY OF PT. INDAH KIAT PULP & PAPER TBK PERAWANG) - Sesilia Grace Sitohang; Harapan Tua RFS (ADISAM PUBLISHER, 2022)
Environmental pollution carried out by PT. Indah Kiat Pulp & Paper Tbk Perawang which occurred in the Siak River basin, Siak Regency, shows that the supervision carried out by the Siak Regency Environmental Service has not been going well. The purpose of this study is to see how the supervision carried out by the Environmental Service of Siak Regency in supervising the environment caused by PT. Indah Kiat Pulp & Paper Tbk Perawang and to see the inhibiting factors for supervision by the Environmental Service of Siak Regency. This research was conducted in Siak Regency using a qualitative descriptive method, and the data collection technique was through observation, interviews and documentation. The results of this study are said to be not optimal, this is because they can still manage waste. This is because there is still waste disposal that is not in accordance with quality standards.